Perception of Role Transition among Final Year Nursing Students in Selected Colleges of Lalitpur - Acharya, Shusma; Gurung, Rabeena (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Role transition is a critical phase for nursing students, marking the shift from academic learning to professional practice. This period is pivotal in shaping their professional identity which influences their future careers in nursing. Thus, the study aimed to assess the final year nursing students’ perception of role transition and association with their socio-demographics variables.Method: Descriptive cross-sectional study design with cluster random sampling method was used. Three CTEVT (Council for Technical Education and Vocational Training) affiliated nursing colleges; Nepal Institute of Medical Science and Technology (NIMST), Shankarapur Academy, and Green Tara College of Health Sciences (GTCHS) were selected.   A total number of 105 Nursing students studying in final year, where 34 from NIMST, 36 from Shankarapur Academy, and 35 from GTCHS were inculded in the study. Standard modified perceptions and expectations of role transition questionnaire was used for measuring the perception of role transition. Descriptive and inferential statistics was used for the analysis. Ethical approval was taken from Nepal Health Care Co-operative Limited/Institutional Review Committee. Data was collected from 2024/06/02 to 2024/06/14.Result: Out of 105 final year nursing students, 69.5% were ≥19 years. Mean age of respondents was 19 ± 1.12. Regarding gender; 99% respondents were female and unmarried. Nursing students with positive perception of role transition was 47.6%. There was no significant association of perception of role transition with socio-demographic variables.Conclusion: Less than half of nursing students have a positive perception of role transition.  There was no any significant association between perception of role transition and socio-demographic characteristics of nursing students.